Code Switching In Instruction: Pre-Service Teachers’ Lived Experiences - Flores, Iulus Rodolfo P.; Balmeo , Myra Christine S. (Future Science / FSH-PH Publications, 2021)
Code switching is really needed in instruction and should be implemented to ensure students’ understanding towards various things (e.g. translating of difficult vocabulary, lessons to be acquired and even in giving instructions), especially for teaching students in lower levels. It can also help in teaching students with multiple intelligences, and in general, makes the pre-service teachers’ life easy inside the room in terms of clarifying things due to any confusion that may arise in the duration of the discussion. This survey interview research explored the Pre-Service Teachers of Ramon Magsaysay Technological University lived experiences in using code switching in instruction. The study found out that the Pre-Service teachers prefer to use code switching in instruction. The Pre-Service teachers believe that using code-switching in class can help them gain students’ interest, manage the class, and make their students understand a particular lesson. Aside from Mattson and Burenholt’s three functions of code-switching, pre-service teachers use code-switching in class so that they can express themselves more during class discussions. The Pre-Service Teachers believe that although code-switching might be useful in class, too much use of it can lead to students being used in speaking their native tongue, thus, weakening the chances to improve their skills in using the English language. The Pre-Service Teachers agreed that there is a higher success in students’ academic achievement when code switching is being applied in instruction. The study recommends that the Department of Education must set clear guidelines regarding the use of code-switching inside an English class. Schools, in all levels, must strengthen their curriculum so that students’ communicative competence will further be developed.